Penyuluhan Mengenai Pemberian MP-ASI Tinggi Protein Hewani Untuk Pencegahan Stunting - Nurjannah Supardi; Hasriani Hasriani; Marlina Azis (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Stunting is a condition of failure to thrive in children under five (for babies under five years of age) which is caused by chronic malnutrition so that the child is too short for his age. Stunting causes children to not reach their maximum height and disrupts brain development which will affect cognitive abilities. One in five children in Indonesia is reported to be stunted. The long-term impact of stunting will cause children to have difficulty receiving lessons, decreased learning achievement, decreased work productivity, low income and minimal participation in community activities. The cause of stunting in toddlers is often the result of many factors related to poverty, including poor diet, health, hygiene and the environment. The current effort being made is to provide education about high protein foods. The education provided aims to enable mothers of toddlers to play a role in providing a healthy, high-protein menu so that it can prevent the incidence of stunting. This community service is carried out with the aim of increasing the knowledge and understanding of mothers of toddlers regarding providing MP-ASI high in animal protein to prevent stunting. It is hoped that after participating in this service activity, mothers of toddlers will be able to provide MP-ASI high in animal protein for toddlers to support their children's height growth.